Regolith mapping and gold geochemical anomalies in the Siguiri Gold Mine of AngloGold Ashanti, Guinea, West Africa - Bah, Boubacar (Rhodes University, Faculty of Science, Department of Geology, 2015)
Gold exploration in the laterite terrains of the Siguiri basin (Guinea-West Africa) is discussed in this thesis. It seeks to propose and develop effective and reliable geochemical exploration techniques applied in such laterite terrains. The study is also intended to investigate and provide some geological clues as to why, in some target areas, the reconnaissance test drilling across the geochemical anomalies couldn't intersect economic gold mineralisation. Targets were generated based on soil geochemical results, some of which were drilled without delivering economic discoveries even on areas with strong and consistent geochemical signatures. To find the failure and define the appropriate methods to be used is the core of the thesis. More importantly, the geological observation is aimed at sourcing and establishing the nature and validity of geochemical anomalies within the license area and their relationship with the underlying lithologies and structural networks. The geological field work conducted during this study is mostly based on regolith and surface geological mapping. The thick laterite cover, deep weathering, bedrock geology, gold geochemistry (the gold geochemical anomalous results are defined according to historical data before 2007), soil formations and variations in climate conditions are emphasized to illustrate the importance of mineral element mobility and dispersion in the weathering profiles. The knowledge and experience in regolith geochemistry and regolith mapping provide the advantage to exploration geologists. The depletion of ore resources and reserves in Siguiri and the continuous decline of the gold price in comparison to the complexity of exploring for gold are demanding more scientific-related thoughts and techniques to be integrated in the available geological, geochemical and geophysical information so as to reduce costs. The integration of good exploration strategy and technique may result in the possibility of making viable discoveries in this highly competitive geological environment where the mineral resources become depleted every day.
Keywords: AngloGold Ashanti Ltd.; Regolith -- Guinea -- Siguiri (Region); Gold mines and mining -- Guinea -- Siguiri (Region); Geochemical surveys -- Guinea -- Siguiri (Region); Soil surveys -- Geochemical methods -- Guinea -- Siguiri (Region); Kriging